The Role of Human Resource Competencies in Enhancing Sustainable Performance of Aquaculture SMEs: The Mediating Effect of Adaptive Capability - Mei Rani Amalia; Agus Suroso; Ratno Purnomo (Ilomata International Journal of Management, 2026)
This study examines the role of human resource competencies in enhancing sustainable performance in aquaculture small and medium-sized enterprises (SMEs) through the mediating role of adaptive capability. In increasingly competitive and uncertain business environments, many aquaculture SMEs face challenges in converting workforce competencies into sustainable long-term performance. Drawing on the Resource-Based View (RBV) and Dynamic Capabilities Theory, this study argues that human resource competencies constitute valuable organizational resources, while adaptive capability enables firms to reconfigure and utilize these resources effectively in response to environmental changes. Unlike prior studies that mainly focus on the direct relationship between human resources and performance, this research highlights adaptive capability as a key mechanism explaining how competencies contribute to sustainable outcomes within the informal human resource context of aquaculture SMEs. Data were collected from 250 owners and employees of aquaculture SMEs and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that human resource competencies significantly enhance adaptive capability (β = 0.56; p < 0.001), and adaptive capability significantly improves sustainable performance (β = 0.39; p < 0.001). Furthermore, adaptive capability partially mediates the relationship between human resource competencies and sustainable performance, suggesting that competencies contribute to performance both directly and indirectly through organizational adaptability. These findings demonstrate that sustainable performance depends not only on workforce competencies but also on the firm's ability to translate those competencies into adaptive operational practices. The study provides important implications for SME managers and policymakers in strengthening competency development and adaptive organizational routines to support long-term business sustainability and resilience.